2011
DOI: 10.5902/198050983231
|View full text |Cite
|
Sign up to set email alerts
|

Espacialização da temperatura do ar anual no estado de Alagoas com diferentes modelos digitais de elevação e resoluções espaciais

Abstract: RESUMOO objetivo do presente trabalho foi estabelecer o modelo digital de elevação e sua resolução horizontal para interpolar a temperatura do ar anual para o estado de Alagoas via modelos de regressão linear múltipla. Ajustou-se um modelo de regressão linear múltipla a séries (11 a 34 anos) de temperatura do ar anual de 28 estações meteorológicas dos estados de Alagoas, Bahia, Pernambuco e Sergipe, em função da latitude, longitude e altitude. Os modelos de elevação considerados nas análises foram o SRTM e o G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
1
9
0
3
Order By: Relevance
“…In ANOVA p<0.05 the model was significant. Similar results using digital elevation models (SRTM) and air temperature were found by Lyra et al (2011) and Oliveira et al (2013). Figure 2 showed that the algorithm applied to determine the land surface temperature, by using the images from MOD11A2 MODIS product, had the best mean statistical indexes for autumn and winter when compared to the data gathered by the Conventional Meteorological Stations in Rio de Janeiro State.…”
Section: Algorithm Testsupporting
confidence: 68%
See 1 more Smart Citation
“…In ANOVA p<0.05 the model was significant. Similar results using digital elevation models (SRTM) and air temperature were found by Lyra et al (2011) and Oliveira et al (2013). Figure 2 showed that the algorithm applied to determine the land surface temperature, by using the images from MOD11A2 MODIS product, had the best mean statistical indexes for autumn and winter when compared to the data gathered by the Conventional Meteorological Stations in Rio de Janeiro State.…”
Section: Algorithm Testsupporting
confidence: 68%
“…Thus, the higher (and lower) temperatures were conditioned by the higher (and lower) altitudes found in the state, indicating geographical influence on the distribution of surface temperature. Lyra et al (2011) observed that, in a tropical region, altitude is the main geographical factor (latitude, longitude and altitude) affecting the distribution of air temperature. With a high temperature nucleus, the Metropolitana region was the only exception to these findings, reflecting the scale of the urbanised areas in this region, itself a consequence of the high level of industrialization.…”
Section: Space-time Distribution Of Surface Temperaturementioning
confidence: 99%
“…No Brasil, embora a falta de observações de longo prazo seja um fator limitante para diagnosticar e quantificar o papel dos diferentes agentes do clima, alguns pesquisadores (KRÜGER (2005);CGEE (2008);FERREIRA et al (2006); MARENGO et al (2006);NOBRE et al (2008);SARTORI et al (2010);LYRA et al (2011)) têm desenvolvido esta técnica e publicado cenários importantes que demonstram as variações climáticas no país.…”
Section: Introductionunclassified
“…As estimativas do método de PM-FAO56, nas condições do estado do Rio de Janeiro avaliadas no presente trabalho, tiveram maior contribuição do seu termo diabático e entre 65 (IGB) e 97 % (Cordeiro -COR), com tendência de aumento dessa fração com a diminuição do déficit hídrico anual. Dessa forma, Apesar da temperatura do ar ser influenciada diretamente pela radiação, outros fatores, como umidade do ar (LYRA et al, 2011), velocidade do vento, nebulosidade (HARGREAVES e SAMANI, 1985, altitude (ALLEN, 1995) e advecção (TABARI; GRISMER; TRAJKOVIC, 2013) também influenciam na sua variação. Esses fatores contribuem para processos não lineares entre radiação e aquecimento do ar, e dessa forma, entre ETo e temperatura do ar.…”
Section: Resultsunclassified